Just Google It: Young Children’s Preferences for Touchscreens versus Books in Hypothetical Learning Tasks - Eisen, Sierra; Lillard, Angeline S. (Frontiers in Psychology, 2016)
Children today regularly interact with touchscreen devices (Rideout, 2013) and thousands of "educational" mobile applications are marketed to them (Shuler, 2012). Understanding children's own ideas about optimal learning has important implications for education, which is being transformed by electronic mobile devices, yet we know little about how children think about such devices, including what children think touchscreens are useful for. Based on a prior result that children prefer a book over a touchscreen for learning about dogs, the present study explored how children view touchscreens versus books for learning an array of different types of information. Seventy children ages 3 to 6 were presented with six different topics (cooking, today's weather, trees, vacuums, Virginia, and yesterday's football game) and chose whether a book or a touchscreen device would be best to use to learn about each topic. Some of this information was time-sensitive, like the current weather; we predicted that children would prefer a touchscreen for time-sensitive information. In addition, each child's parent was surveyed about the child's use of books and touchscreens for educational purposes, both at home and in school. Results indicated that younger children had no preference between books and touchscreen devices across learning tasks. However, 6-year-olds were significantly more likely to choose the touchscreen for several topics. Surprisingly, 6-year-olds chose a touchscreen device to learn about time sensitive weather conditions, but not yesterday's football. Children's choices were not associated with their use of books and touchscreens at home and school.